Coronary Stent Graft for Treatment of Right Internal Mammary Artery Pseudoaneurysm - Abhay Krishna; Priti Singhania (Heart Views)
We report a case of partially thrombosed pseudoaneurysm of the right internal mammary artery (IMA) in a 20-year-old male, following penetrating chest wall trauma with a steel wire. He presented with a swelling over the anterior aspect of the right side of the chest. Ultrasonography showed that swelling was communicating with the right IMA. Computed tomography angiography of the chest further revealed it to be partially thrombosed pseudoaneurysm of the right IMA. Pseudoaneurysm was successfully treated percutaneously using 2.75 mm × 19 mm coronary stent graft (GraftMaster, Abbott Vascular). This case highlights the successful use of less invasive percutaneous technique for the management of IMA pseudoaneurysm.